English as a second language for elderly learners; Лингвистические и культурологические аспекты современного инженерного образования - Новикова В. С. Вера Станиславовна (2023, 2023)
The relevance of the study is determined by the educational paradigm change in higher education institutions, namely the transition from classical to innovative educational paradigm. This is especially important for the elderly teachers, on the example of Tomsk polytechnic university (TPU). The research focuses on practical approaches to teaching English to senior learners in the Russian system of higher education.